Heartburn: mitigating wildfire risk to interface communities in America's heartland - Ochsner, Landon (Kansas State University, 2024)
The simultaneous growth of wildfires and developed areas creates increasing conflict between human settlements and destructive natural systems. While wildfire mitigation strategies have been explored widely in recent decades, less attention has been paid to their application in the grasslands of the Great Plains of the United States, where wildfire risk is increasing. This study addresses this issue by identifying wildland-urban interface typologies, examining wildfire perceptions and mitigation preferences of residents and industry professionals in the region, and proposing design and planning strategies for wildfire mitigation. More specifically, this study investigates the application of these mitigation preferences and precedents to the identified Great Plains wildland-urban interface typologies. This study identifies common arrangements of built and natural landscape factors of the wildland-urban interface in Manhattan, Kansas. It then conducts community and expert surveys among residents of Manhattan and fire professionals across the Great Plains region, respectively. These outcomes are applied to typologies developed from the study of landscape factors to mitigate Great Plains wildfire risk at the city, neighborhood, and individual household scales. The results of this research offers insight into the physical makeup of the Great Plains wildland-urban interface, the risk perceptions of Great Plains residents, and mitigation preferences among the region’s wildfire professionals. It then utilizes this information to envision the conceptual application of mitigation strategies to the identified typologies.
Keywords: Wildfire mitigation; Urban design; Wildland-urban interface (WUI); Great Plains wildfire risk; Land-use planning; Disaster resilience